Pengaruh Pemberian Air Cucian Beras dan Pupuk Organik Cair (POC) Terhadap Pertumbuhan Stek Tanaman Jambu Air Madu (Syzygium equaeum Burn F. Alston) - Andika Rinaldy; Yusriani Nasution; Meiliana Friska (Journal Agro-Livestock, 2024)
The water guava Syzygium equaeum is a plant in the guava family or Myrtaceae originating from Indonesia and Malaysia.  The water guava tree and fruit are not much different from other water guava (S. aqueum), some of the cultivars are even difficult to distinguish, so both are often named by the common name water guava or just guava. Cutting is a vegetative propagation technique by cutting the vegetative part to grow into an adult plant whose characteristics are similar to those of the parent. Rice water washing waste is a waste product originating from a production process, both industrial and domestic (household) which no longer has economic value. Rice washing water contains many nutrients dissolved in it, including 80% vitamin B1, 70% vitamin B3, 90 % vitamin B6, 50% manganese, 50% phosphorus, 60% iron. The method in this research was a Non Factorial Randomized Block Design with six treatments and four replications, namely B0 = Control, B1 = 0.25 liters of rice/polybag washing water, B2 = 0.50 liters of rice/polybag washing water, B3 = 0.25 liter POC/polybag, B4 = 0.50 liter POC/polybag B5 = 0.50 liter /polybag rice washing water + 0.50 liter POC. The results of the study showed that the provision of rice washing water and POC on the growth of honey water guava only had an effect which was significant in the parameters of age at germination, while the parameters of growth percentage, number of shoots and number of leaves showed no significant influence. The best treatment is B5, namely giving rice washing water + POC.